Firms' Financing Dynamics around Lumpy Capacity Adjustments - Christoph Görtz; Plutarchos Sakellaris; John D. Tsoukalas (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study how firms adjust their financial positions around the times when they undertake lumpy adjustments in capital or employment. Using U.S. firm level data, we document systematic patterns of cash and debt financing around lumpy adjustment, remarkably similar across capital and employment. Firm specific fundamentals in Tobin's Q, profitability and productivity are leading indicators of the lumpy adjustment. Cash and debt capacity are actively manipulated, and contribute significantly quantitatively, to increase financial resources in anticipation of the expansion of firm capacity. Lumpy contractions in productive capacity are undertaken following years where firms reduce cash balances and hold above average levels of debt. During and after contractions, firms rebuild cash and reduce debt growth significantly in a concerted effort to restore financial resources by adjusting their productive operations.
Keywords: G30; G32; E32; 330; lumpy adjustment; firm capital and employment dynamics; leverage; debt; cash